Coding for MIMO-OFDM in Future Wireless Systems - Ahmed, Bannour (Springer, 2015)
This book introduces the reader to the MIMO-OFDM system, in Rayleigh frequency selective-channels. Orthogonal frequency division multiplexing (OFDM) has been adopted in the wireless local-area network standards IEEE 802.11a due to its high spectral efficiency and ability to deal with frequency selective fading. The combination of OFDM with spectral efficient multiple antenna techniques makes the OFDM a good candidate to overcome the frequency selective problems.